Application of omics technologies for a deeper insight into quali-quantitative production traits in broiler chickens: A review - Zampiga, Marco (J Anim Sci Biotechnol, 2018)
The poultry industry is continuously facing substantial and different challenges such as the increasing cost of feed ingredients, the European Union’s ban of antibiotic as growth promoters, the antimicrobial resistance and the high incidence of muscle myopathies and breast meat abnormalities. In the last decade, there has been an extraordinary development of many genomic techniques able to describe global variation of genes, proteins and metabolites expression level. Proper application of these cutting-edge omics technologies (mainly transcriptomics, proteomics and metabolomics) paves the possibility to understand much useful information about the biological processes and pathways behind different complex traits of chickens. The current review aimed to highlight some important knowledge achieved through the application of omics technologies and proteo-genomics data in the field of feed efficiency, nutrition, meat quality and disease resistance in broiler chickens.